TEKNIK PENCARIAN RUMAH SEWA YANG DIREKOMENDASIKAN DENGAN METODE LOCATION BASED SERVICE DAN MULTI-ATTRIBUTE DECISION MAKING (STUDI KASUS: RUMAH SEWA DI SEKITAR UIKA BOGOR) - Setiawan, Foni Agus; Laxmi, Gibtha Fitri; Abidin, Riswan (Krea-TIF: Jurnal Teknik Informatika, 2014)
Universitas Ibn Khaldun Bogor (UIKA) is a growing campus. The number of students who register have increased from year to year. The registrant does not only come from Bogor, but many also come from outside the city such as Jakarta, Sukabumi, and Cianjur, even outside Java. Students who come from outside the city will need residence as a rental house or called boarding house near the campus, which can be reached on foot or with a quick and inexpensive transportation. Due to the lack of information regarding the location where rental houses that are around UIKA, then the location of the rental housing search process is quite time consuming when done by asking or touring around the campus. This study aims to create a location-based service applications that can provide the information of spread points of the rental housing at a radius of 1000 meters from UIKA. The method used in this study is a Location Based Service that is used to determine the user's location and provide services that are close to the user's location. Method of Multi-Attribute Decision Making is used to consider the factors in the selection of recommended rental houses, such as: distance, price, comfortability, facilities, and ease of access. Results of this research is the android-based application of rental houses information that can provide presence information of rental houses around UIKA and recommend the best rental house based on the factors consideration. The existence of this application is expected to assist students in finding the best rental house around campus UIKA.